Prognosis of Pancreatic Cancer Patients with Synchronous or Metachronous Malignancies from Other Organs Is Better than Those with Pancreatic Cancer Only - Shin, Su-Jin; Park, Hosub; Sung, You-Na; Yoo, Changhoon; Hwang, Dae Wook; Park, Jin-hong; Kim, Kyu-pyo; Lee, Sang Soo; Ryoo, Baek-Yeol; Seo, Dong-Wan; Kim, Song Cheol; Hong, Seung-Mo (Cancer research and treatment, 2018)
Pancreatic cancer associated double primary tumors are rare and their clinicopathologic characteristics are not well elucidated. Clinicopathologic factors of 1,352 primary pancreatic cancers with or without associated double primary tumors were evaluated. Of resected primary pancreatic cancers, 113 (8.4%) had associated double primary tumors, including 26 stomach, 25 colorectal, 18 lung, and 13 thyroid cancers. The median interval between the diagnoses of pancreatic cancer and associated double primary tumors was 0.5 months. Overall survival (OS) of pancreatic cancer patients with associated double primary tumors was longer than those with pancreatic cancer only (median, 23.1 months vs. 17.0 months, p=0.002). Patients whose pancreatic cancers were resected before the diagnosis of metachronous tumors had a better OS than patients whose pancreatic cancer resected after the diagnosis of metachronous tumors (48.9 months and 13.5 months, p=0.001) or those whose pancreatic cancers were resected synchronously with non-pancreas tumors (19.1 months, p=0.043). The OS of pancreatic cancer patients with stomach (33.9 months, p=0.032) and thyroid (117.8 months, p=0.049) cancers was significantly better than those with pancreas cancer only (17.0 months). About 8% of resected pancreatic cancers had associated double primary tumors, and those from the colorectum, stomach, lung, and thyroid were common. Patients whose pancreatic cancer was resected before the diagnosis of metachronous tumors had better OS than those resected after the diagnosis of metachronous tumors or those resected synchronously.